Dietary supplements quality analysis tools from the United States Pharmacopeia. Issue 3 (9th February 2016) - Sarma, Nandakumara; Giancaspro, Gabriel; Venema, Jaap
Abstract : The United States Food and Drug Administration (FDA) issued the dietary supplement (DS) current good manufacturing practice (GMP) regulations in compliance with the mandate from the Dietary Supplements Health and Education Act (DSHEA), with the intention of protecting public health by ensuring the quality of DS. The GMP regulations require manufacturers to establish their own quality specifications for identity, purity, strength, composition, and absence of contaminants. Numerous FDA‐conducted GMP inspections found that the private specifications set by these manufacturers are often insufficient to ensure adequate quality of dietary ingredients and DS. Wider use of the public standards developed by the United States Pharmacopeial Convention (USP), in conjunction with GMP compliance, can help ensure quality and consistency of DS as they do for medicines. Public health protection could be enhanced by strengthening the GMP provisions to require conformance with relevant United States Pharmacopeia–National Formulary ( USP–NF ) standards, or in the absence of USP standards, other public compendial standards. Another serious concern is the presence of synthetic drugs and drug analogues in products marketed as DS. Use of the new USP General Chapter Adulteration of Dietary Supplements with Drugs and Drug Analogs <2251> may reduce the exposure of consumers to dangerous drugs disguised as DS. © 2016 The Authors. Drug Testing and Analysis published by John Wiley & Sons Ltd. Abstract : The dietary supplement (DS) good manufacturing practice (GMP) regulations require manufacturers to establish their own quality specifications. GMP inspections found that the private specifications are often insufficient to ensure adequate quality. Another serious concern is the presence of synthetic drugs and drug analogs in products marketed as DS. Wider use of the public standards developed by the United States Pharmacopeial Convention (USP), in conjunction with GMP compliance, can help ensure quality and consistency of DS as they do for medicines.